Comparison Between Serial and Independent Questions: A Psychometric and Methodological Approach - Víctor Hugo Olmedo Canchola; José Gamaliel Velazco González; Gustavo Quiroga Martínez (Journal of Medical Education and Curricular Development)
Objective To determine if statistical and psychometric outcomes differ between tests composed of serial and independent questions. Specific goals include assessing which format provides better reliability and validity, understanding response patterns, and comparing difficulty and discrimination indices under classical test theory. Methodology The study involved a single-group design with spiral counterbalance, allowing examinees to answer both formats within a single exam of 220 items. Of these, 200 were independent questions, and 20 were organized into 4 clinical cases with 5 related items each. The exam was administered by computer to anesthesiologists undergoing certification or recertification. Results From 2109 candidates, the analysis showed significant differences in internal consistency, with Cronbach's alpha of .790 for independent questions and .527 for serial questions. A moderate positive correlation ( r  = .488) between scores in the 2 formats was observed. No significant difference was found in difficulty and discrimination indices between formats. Discussion Independent questions showed higher reliability, likely due to their lack of dependency, making them more suitable for high-stakes exams. Serial questions, while valuable for assessing integrative reasoning, introduce dependency that affects consistency and may skew outcomes when the initial question is answered incorrectly. Despite similar difficulty and discrimination indices, the unique dependency in serial questions affects their suitability for high-stakes testing. Conclusions Independent questions provide a more reliable format for high-stakes exams, but serial questions can enhance assessments by probing various aspects of clinical reasoning within a single case. A balanced approach incorporating both formats may optimize the reliability and validity of medical certification exams, leveraging the strengths of each question type.